1990
DOI: 10.1007/bf00046340
|View full text |Cite
|
Sign up to set email alerts
|

Tumor progression: Potential role of unstable genomic changes

Abstract: It is generally accepted that the genome of tumor cells is less stable than that of most normal cells, and it has been hypothesized that this genomic instability is probably involved in the process of tumor progression. However, the rate of occurrence of classical spontaneous mutations in tumor cells is too low to account for the rapid changes that can occur during tumor progression. Thus it is likely that other types of changes, such as gene amplification, must be involved in tumor progression. Gene amplifica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
44
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(44 citation statements)
references
References 39 publications
0
44
0
Order By: Relevance
“…This process is termed the malignant progression of tumours and is probably a result of the genomic instability of tumour cells (Hill, 1990). Recent studies have suggested that microenvironmental conditions known to occur in tumours, such as hypoxia and reoxygenation, might increase the genomic instability and hence promote the malignant progression (Hill, 1990;Brown and Giaccia, 1994;Dachs and Stratford, 1996;Hlatky et al, 1996). The study reported here suggests that hypoxia might also promote the malignant progression by increasing the angiogenic potential of tumour cells through increased synthesis and secretion of VEGF.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This process is termed the malignant progression of tumours and is probably a result of the genomic instability of tumour cells (Hill, 1990). Recent studies have suggested that microenvironmental conditions known to occur in tumours, such as hypoxia and reoxygenation, might increase the genomic instability and hence promote the malignant progression (Hill, 1990;Brown and Giaccia, 1994;Dachs and Stratford, 1996;Hlatky et al, 1996). The study reported here suggests that hypoxia might also promote the malignant progression by increasing the angiogenic potential of tumour cells through increased synthesis and secretion of VEGF.…”
Section: Discussionmentioning
confidence: 99%
“…Reoxygenation of hypoxic cells occurs during unperturbed tumour growth as a result of reopening of temporarily closed vessels and during therapy as a result of therapy-induced tumour cell inactivation (Kallman, 1972;Brown, 1979;Chaplin et al, 1987). Hypoxia followed by reoxygenation might promote the malignant progression of tumours (Hill, 1990). Thus, tumour cells exposed to hypoxia in vitro can show increased expression of several selected genes, including genes encoding cell cycle-regulatory proteins, haematopoietic and/or vascular regulatory proteins, metastasis-promoting proteins, viral proteins, metabolic enzymes and transcription factors (Brown and Giaccia, 1994;Dachs and Stratford, 1996).…”
mentioning
confidence: 99%
“…Tumor hypoxia selects p53 À/À transformed cells and thereby expands cells with diminished apoptotic potential in vitro (Graeber et al, 1996). These mechanisms all together are likely to influence the malignant progression of tumor cells (Hill, 1990;Russo et al, 1995;Graeber et al, 1996;Coquelle et al, 1998;Dachs and Chaplin, 1998). Besides, since hypoxic tumor cells cease to divide, they are resistant to conventional radiotherapy and chemotherapy (Rice et al, 1986;Young and Hill, 1990;Teicher, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…The malignant progression of tumours is also influenced by the metabolic microenvironment of the tumour cells (Hill, 1990). The expression of several specific genes involved in the malignant progression is increased in hypoxic tumour cells and tumour cells at low PH.…”
mentioning
confidence: 99%
“…The probability of microenvironment-induced tumour treatment failure or malignant progression is influenced by the ability of the tumour cells to withstand severe energy deprivation during prolonged exposure to hypoxia at normal or low PHe (Coleman, 1988;Tannock and Rotin, 1989;Vaupel et al, 1989;Hill, 1990). The energy status of tissues is controlled by the balance between the rates of ATP formation and utilization.…”
mentioning
confidence: 99%